Implementasi Pendidikan Karakter pada Siswa Sekolah Dasar - Susan Febriantina; Dinda Anggrayni Riswono; Lala Aprilia; Sabrina -; Siti Ukhfiya (JURNAL PEDAGOGIK PENDIDIKAN DASAR, 2021)
Character is very closely related to religious, psychological, moral and character values that distinguish a person from others. In this era of globalization, moral shifts are rife which result in the loss of character of Indonesian children. For this reason, education needs to take part in building character education in children, so that Indonesian children can become individuals who have characters that are in accordance with their national identity. This study aims to examine and find out how the implementation of character education in elementary school students. Our research uses a qualitative approach with a literature study method, namely collecting existing theories and concluding them into new theories. From this study we found that character education can be applied in elementary schools through methods of applying character values during learning, learning methods outside the classroom, helping disaster victims, and solving problems/cases that make students think critically to solve them.